Measurement of 3-dimensional pole plant forces in an elite pole-vaulter over various approach distances - Doyle, M.; Warburton, T.; Lyttle, A.; James, R.; Alderson, J. (Procedia Engineering, 2011)
This paper presents pilot data derived from a newly installed 3-dimensional instrumented pole plant box and offers comparisons between the forces produced in vaults performed over three difference approach distances. Data was collected from an elite male pole vaulter performing 2-step, 4-step and 8-step approaches, with the resulting force profiles compared to determine differences in forces produced during the vaults. Utilising the force data a typical vault was characterised into four phases. Noticeable force increases were observed in the two horizontal planes as the approach distance increased, especially in the first and third phases of the vault. Timing changes in the phases of the vault were also observed, with the second phase of the vault decreasing in time and the third phase increasing in duration as the approach distance increased. Further investigation is required, however it appears the middle two phases are the most likely to change with different vaults, and therefore may be crucial to the execution of successful jumps in pole vault.